Long‐Ranging Movements of Asiatic Lions: Implications for Conservation and Management in Gujarat, India - Mohan Ram; Aradhana Sahu; Nityanand Srivastava; Rohit Chaudhary; Lahar Jhala; Yashpal Zala (Ecology and Evolution, 2025)
ABSTRACT Effective conservation and management of large carnivores in landscapes shared with humans require a comprehensive understanding of their habitat selection and movement patterns. The Asiatic lion (Panthera leo persica), an endangered species, has experienced population growth and expansion beyond the Gir Forest. This study investigates the factors influencing the habitat selection and movement patterns of lions undertaking long‐distance movements in shared landscapes, providing insights for their long‐term conservation and management. We tracked the movement patterns and habitat selection of 10 Asiatic lions using satellite collars. Movement metrics, including distance traveled, were analyzed across different habitats during the day and night. Space use was evaluated by assessing the time lions spent in various habitats, with core area preferences analyzed using the 50% fixed kernel and Jacob's preference index. Fine‐scale habitat use during day and night was analyzed using the integrated step selection function. Lions moved significantly more distance at night (11.07 ± 0.19 km) than during the day (2.28 ± 0.05 km). In core areas of their home ranges, they showed a strong preference towards orchards, followed by forests and water bodies, while avoiding built‐up areas and cropland. The integrated step‐selection function indicated that habitat selection was positively associated with natural habitats such as forests, wastelands, and water bodies (day: 3.31 ± 0.32; night: 0.50 ± 0.12). Conversely, built‐up areas negatively impacted habitat use (day: −0.45 ± 0.41; night: −0.93 ± 0.14), with orchards (day: 2.83 ± 0.33; night: −0.14 ± 0.13) and cropland (day: 1.42 ± 0.32; night: −0.86 ± 0.12) showing variable selection between day and night. Lions in shared landscapes traveled greater distances during the night, likely to avoid human disturbances. Natural habitats—forests, wastelands, and water bodies—are crucial for their space use and habitat selection, underscoring the importance of these areas for their long‐term conservation and management.